Protective Effect of Resveratrol on Knee Osteoarthritis and its Molecular Mechanisms: A Recent Review in Preclinical and Clinical Trials - Yang, Shenglei; Sun, Mingli; Zhang, Xinan (Frontiers in Pharmacology, 2022)
Osteoarthritis (OA) is one of the progressing chronic joint associated with by many complex factors such as age, obesity, and trauma. Knee osteoarthritis (KOA) is the most common type of OA. KOA is characterized by articular cartilage destruction and degeneration, synovial inflammation, and abnormal subchondral bone changes. To date, no practical clinical approach has been able to modify the pathological progression of KOA. Drug therapy is limited to pain control and may lead to serious side effects when taken for a long time. Therefore, searching for safer and more reliable treatments has become necessary. Interestingly, more and more research has focused on natural products, and monomeric compounds derived from natural products have received much attention as drug candidates for KOA treatment. Resveratrol (RES), a natural phenolic compound, has various pharmacological and biological activities, including anti-cancer, anti-apoptotic, and anti-decay. Recently, studies on the effects of RES on maintaining the normal homeostasis of chondrocytes in KOA have received increasing attention, which seems to be attributed to the multi-targeted effects of RES on chondrocyte function. This review summarizes preclinical trials, clinical trials, and emerging tissue engineering studies of RES for KOA and discusses the specific mechanisms by which RES alleviates KOA. A better understanding of the pharmacological role of RES in KOA could provide clinical implications for intervention in the development of KOA.